THE ROLE OF THE COMMUNITY CENTER (BAPAS) IN THE ACCOMPANYING AND SUPERVISION OF CHILDREN PERFORMING CRIMES OF SEXUAL ABUSE Regarding the Decision of the Madiun Regency District Court Case Number 6/Pid.Sus Anak/2019/PN.Mjy - Nugroho, Bambang Eko; Hastari, Tri Anggis (Activa Yuris: Jurnal Hukum, 2024)
Children are the young generation and the foundation of the nation's hopes. Children are the successors of the ideals of the nation's struggle who have a strategic role and have special characteristics and traits that are expected to ensure the continued existence of the nation and state in the future. Children need to have the widest possible opportunities to grow and develop optimally, both physically, mentally and socially, and have noble morals. Children are an inseparable part of human survival and the survival of a nation and state. In the Indonesian Constitution, children have a strategic role which is explicitly stated that the state guarantees every child's right to survival, growth and development as well as protection from violence and discrimination. Children are not miniature adults, so based on the characteristics and characteristics of children, it is necessary to differentiate treatment. This is intended to better protect and protect children so they can face their future. With all the potential they have, it is not impossible that today's children will play a role in increasing the rate of national development in the future. For the continued growth of children, both mentally and physically, through interaction in society, children must really receive special attention. Apart from that, the treatment of children must really be paid attention to and treated carefully and conceptually so that the potential inherent in children can grow and develop well and in balance. Children are subjects who have feelings, thoughts, desires and self-esteem. They must be given the opportunity to be heard and have their opinions respected in matters concerning their interests. The rapid development of the world is nothing but the result of the development of human thought, both providing positive and negative impacts. The mentality of children who are still in the stage of finding their identity is sometimes easily influenced by the situation and environmental conditions around them. So if the environment where the child is in is bad, they can be influenced by actions that may violate the law. This of course can be detrimental to himself and society. Not a few of these actions ultimately got them into trouble with law enforcement officials.